The Level Of Anthropogenic Impact On Ecosystems As A Function Of Properties Of Plant Associations - A. V. Lindiman; S. A. Buimova; L. V. Shvedova; A. P. Kupriyanovskaya; A. V. Nevsky (Тонкие химические технологии)
The approach of estimation of a level of anthropogenic impact on ecosystems as a function of properties of plant associations has been proposed. In the course of investigation it was established that it is possible to estimate the growth degree of anthropogenic impact on ecosystem by: the increase part of a ruderal vegetation in common composition of plant associations; the increase amount of a ruderal vegetation growing on one square meter of soil surface (thickness of sowing); the increase of lead and cadmium content in above ground part of the plants. The sufficiently high ability of lead extraction from soil by such plants-accumulators as great nettle and meadow fescue has been established